Baptist Identity in a Christian Welfare State: A Swedish Case Study - Wenell, Fredrik (Baptist quarterly, 2025)
The Swedish welfare state emerged during the 1950s at the same time as Swedish Baptist identity was undergoing change. Swedish Baptist identity had previously been based on the notion that the congregation was of itself a social body, but over time an ecclesiology arose which made an emotional conversion central, and thus faith became primarily an individual affair. This article argues that in the Swedish context this change was enhanced through a negotiation between the emerging welfare state and a revivalist theology. To uphold a bold Baptist identity, a contemporary Swedish Baptist ecclesiology must therefore develop a theology that both acknowledges the positive values in a welfare state and at the same time continues to argue for a radical religious freedom where the existence of various forms of alternative societal bodies is recognised by the state, particularly in the current multicultural context.